If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + x + 3x + (3x + -7) = 13 Reorder the terms: x + x + 3x + (-7 + 3x) = 13 Remove parenthesis around (-7 + 3x) x + x + 3x + -7 + 3x = 13 Reorder the terms: -7 + x + x + 3x + 3x = 13 Combine like terms: x + x = 2x -7 + 2x + 3x + 3x = 13 Combine like terms: 2x + 3x = 5x -7 + 5x + 3x = 13 Combine like terms: 5x + 3x = 8x -7 + 8x = 13 Solving -7 + 8x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 8x = 13 + 7 Combine like terms: -7 + 7 = 0 0 + 8x = 13 + 7 8x = 13 + 7 Combine like terms: 13 + 7 = 20 8x = 20 Divide each side by '8'. x = 2.5 Simplifying x = 2.5
| 5z(z-6)+4(z-6)= | | 5n-8=2n+19 | | x+x+3x+(3x-5)=20 | | x+x+2x+(2x-5)=12 | | y=-24x+379 | | 2/5x-7/6x(-7) | | 4[8-(-7x-7)]=252x+284 | | 6y-27=-13+4y | | 4x^5-32x^2y^3= | | 4r-22=-25+r | | (4x-5y)= | | -5/9=w-(3/4) | | 6/7=3/v | | 24/8=60/m | | 16/10=m/35 | | 9/4w=-48 | | 9y^3-9y^2-4y+4=0 | | Cos(8*x)=1 | | x+x+2x+(2x-5)=13 | | 9y^3+18y^2-16y-32=0 | | -1/6(5x-1)=5/3(x-7) | | y=2x+9.74 | | (4x+5y)= | | 3x=(2x-2)(m+4)forx | | 3/-5s=-40 | | 2x+7z=4+7y | | 2(3-10x)+4(5x+2)=6 | | (10x^4/y)/(4x^5y/3y^4) | | (W+4)(w-6)=0 | | 5z-25=-40+2z | | 3x+7=-50 | | 7m-28=-22+6m |